The Dynamics of Family Law in Indonesia: Bibliometric Analysis of Past and Future Trends - Maimun, Maimun; Anggriani, Jum; Harlina, Indah; Suhendar, Suhendar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
Family law is a branch of law that regulates relationships and interactions between family members. Because underlying family law are a number of factors that reflect the complexity and diversity of societies as well as different cultural values throughout the world. This research aims to carry out an indepth analysis of certain aspects of family law, such as regulations on marriage, divorce, child custody or family inheritance. This analysis can include a study of legal developments, comparisons with other legal systems, and evaluation of the effectiveness of implementing regulations, then understanding how social changes and changes in values in society affect family law. The method used is bibliometric analysis with a systematic literature review approach, there are 72 documents originating from Scopus metadata. Family law publications have increased from year to year over a period of 20 years, in 2011 there were 39 publications regarding family law, then they fell again in line with little attention to aspects of family law, from 2015 to the peak in 2020 there were 77 publications which has been published. Factors that cause this are due to social change, technological progress, and the evolution of societal values, social change. Increased awareness of individual rights, especially the rights of women and children, has encourage interest in change and reform of family law and Globalization brings new ideas and cultural influences that can influence the way family law is viewed. Research findings may have limitations in terms of applicability or relevance if laws or policies change. Family law is subject to continuous change and adaptation, particularly in response to changes in society and values. Research may not always be able to capture or respond quickly to changes.